2013 25th Chinese Control and Decision Conference (CCDC) 2013
DOI: 10.1109/ccdc.2013.6561200
|View full text |Cite
|
Sign up to set email alerts
|

An employment contract with fairness preference

Abstract: This paper explores the problem of principal's optimal decision on employment contract design, from the principal's perspective of maximizing the expected welfare in an uncertain environment with one principal and two agents, where both the two agents have properties of fairness preference. By describing the agents' effort as random variables, and devising the contract as a vector with two dimensions: fixed wage variable and share proportion variable, a new employment contract model with fairness preference is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Fehr and Schmidt (2010) have indicated that the fairness preference model plays an important role in solving the puzzle of why most experimental subjects behave very selfishly in some games, by free-riding in the final periods of voluntary cooperation games, for example, and exploiting their bargaining power in competitive market games, while they demonstrate conversely "fair" behavior in other scenarios, such as in trust games, in bilateral bargaining games and in public good games with punishments. Song et al (2013) designed a new employment contract model to reflect fairness preference. They found that the agents' optimal efforts were undertaken independently where there was a fixed wage, but their efforts increased relative to the share proportion available to them.…”
Section: Introductionmentioning
confidence: 99%
“…Fehr and Schmidt (2010) have indicated that the fairness preference model plays an important role in solving the puzzle of why most experimental subjects behave very selfishly in some games, by free-riding in the final periods of voluntary cooperation games, for example, and exploiting their bargaining power in competitive market games, while they demonstrate conversely "fair" behavior in other scenarios, such as in trust games, in bilateral bargaining games and in public good games with punishments. Song et al (2013) designed a new employment contract model to reflect fairness preference. They found that the agents' optimal efforts were undertaken independently where there was a fixed wage, but their efforts increased relative to the share proportion available to them.…”
Section: Introductionmentioning
confidence: 99%